PENGARUH PRODUK DAN PELAYANAN TERHADAP TINGKAT KEPUASAN PELANGGAN ( Studi Kasus Pada Toko Escada Pasar Tanah Abang Blok A ) - iwan asmadi (Widya Cipta - Jurnal Sekretari dan Manajemen, 2017)
Tanah Abang Center of Grocery is the most famoust grocery of  people, even local or international. There is so many trader of tekstile and Escada shop is the ones.  Because so many trader at there, so the compete is so tight. Therefore the trader must be demanded for willing the best product and give the best service. The kind of product or price can be the same between the trader. To take the consument the different is good service that make  costumer being satisfied and be glad when take a shop at  Escada. The costumer satisfied is the most important factor for every kind of business that must be kept, that the hopes and the needs of customer can be take over there.             This research is to purpose for knowing about product influence to take costumer satisfaction, and the influence of service to take customer satisfaction. Than product influence and service  in the same time to take customer satisfaction at  Escada shop. The methode of this research  is survey methode,  with take the simple sample random sampling.            Based of  survey result that have done, take the tabulation and data-processing with computer program SPSS 15.0 for windows. There is so significan between product and costumer satisfaction . It can be from test calculation t that t hitung about 3,410 bigger than t tabel about 2,011. so can be sayed that product varible   with costumer satisfaction variable is be significant influeced that the meaning is the willing of product can be make the customer satisfaction. The influence of service dan costumer satisfaction can be see at t that t is about 38,906 bigger than t table about 2,011. Can be sayed that costumer variable with customer satisfaction variable have a significant relationship, that means good service can be make costumer satisfaction can be better.